Cognitive and social cognitive function in patients with schizophrenia and affective disorder: effects of combining pharmacotherapy with cognitive remediation - G. Sachs; A. Erfurth (European Psychiatry, 2024)
Introduction In recent decades, there has been increasing interest in neurocognitive function, including non-social and social cognition. Cognitive impairment has a significant impact on functional outcome, especially in schizophrenic disorders, but also in affective and other psychiatric disorders.